Characterization of medium density particleboards using agricultural residues - Valarelli, Ivaldo de Domenico; Battistelle, Rosane Aparecida Gomes; Bezerra, Barbara Stolte [UNESP]; Branco, Luiz A. Melgaço N.; Chahud, Eduardo; Christoforo, André Luis; Rocco Lahr, Francisco Antonio (My University, 2015)
In recent years the production of products derived from wood and bamboo are increasing, due to the search for a more rational exploitation of these raw materials. Amongst these products, the particleboards production combine sustainability and rationality in the use of these materials. In this context, this work has the objective to study the application of alternative raw materials in the manufacture of Medium Density Particleboards (MDP), using residues from industrial processimg of coffee and bamboo. MDP had been produced with particles of giganteus bamboo of the Dendrocalamus species and particle of coffee rind in the intermediate layer of the particleboard, bonded with polyurethane resin based on castor oil. The physical and mechanical characterization was carried out accordingly to NBR 14810-3 (2006). The physical properties evaluated were: of water absorption for 2h and 24h; thickness swallowing for 2h and 24h; density, humidity content. The mechanical properties evaluated were: Tensile strength, static bending (MOR and MOE). The results were compared with NBR 14810-2 (2006) and also with the ANSI A208-1 (1993). The physical performance of these particleboards was below the values recommend by the Brazilian norm. Also the mechanical characteristics are not improve, demonstrating that the inclusion of coffee rind did not benefit the physical characteristics and nor the mechanical ones. However it can be used as construction materials for partitions and ceiling panels.
Keywords: Bamboo; Coffee rind; Particleboard; Residues